Demokrasi, Pilkada Langsung Dan Kelangsungan Otonomi Daerah - Hendrikus Tri Wibawanto Gedeon (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2007)
Indonesia has been attemping to develope democratic political system throught the country. One among instruments to achieve this is through implementing direct vote. Direct vote is expected to be able to promote democratic local governance as well as prime public service. In implementation, direct vote should be conducted so as not to upset the ultimate goals of autonomy policy. This is due some potential threats which may intervene, or even destroy the process. The threats are comprised of three forms: fisrt, the transition state of local people toward democracy without reliable political structure and political figures; second, plural societies in terms of ethnics, race, languange and religionâ€”yhis may trigger internal conflict; and third, excessive political marketing â€“ a local public figure may publicly be voted for his/her â€engineered appealsâ€ not for his/her competence. Despite these, if political societies are able to manage the three unfavorable environments wisely, the ultimate goals of local autonomy may eventually be achieved.